Capacidade competitiva de goiabeira e plantas daninhas na fase inicial de crescimento - Melo, Marlenildo Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
Considering the higher guava sensibility after transplanting, and the difference on weed competiveness, it was hypothesized that the coexistence with these plants may negatively alter crop development. Thus, this work aimed to evaluate the effects on growth components and nutrient accumulation of guava and Bidens subalternans DC., Waltheria indica L. and Commelina benghalensis L. in competition. Therefore, an experiment was carried out in a greenhouse using a randomized block design with four replications. The species were cultivated in coexistence (guava + B. subalternans; guava + W. indica; guava + C. benghalensis) and isolated for 60 days. After coexistence, we determined: number of leaves per plant; stem diameter; shoot and root height; leaf area; and dry matter and nutrients accumulation in different organs (leaves, stems, roots and total) of guava and weeds. The results indicated that W. indica and C. benghalensis were more aggressive to guava after transplant, reducing growth and nutrient accumulation of crop
Competitive capacity of guava and weeds in the initial growth
Keywords: Bidens subalternans DC.; Commelina benghalensis L.; Crescimento; Psidium guajava L.; Waltheria indica L.; Bidens subalternans DC.; Commelina benghalensis L.; Growth; sidium guajava L.; Waltheria indica L.; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA